2004
DOI: 10.1159/000081111
|View full text |Cite
|
Sign up to set email alerts
|

How Do Dermatological Vehicles Influence the Horny Layer?

Abstract: Emulsifying agents in aqueous solution lead to dehydration of the horny layer of the epidermis and damage to the barrier. This is only partly true if emulsifying agents are constituents of emulsions. Water-in-oil (W/O) emulsions cause an improvement in the hydration of the horny layer and barrier function. In the case of an additional effect of wash solutions, a partial or complete abolition of the drying out and barrier-damaging effect of the wash solution results. Oil-in-water (O/W) emulsions without glycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…A possible improvement of acne skin due to the drying effect of heat and water of sauna bathing is mentioned in the literature [23, 24]. Our results showed a lowered casual sebum content on the forehead of skin in the RSG.…”
Section: Discussionsupporting
confidence: 68%
“…A possible improvement of acne skin due to the drying effect of heat and water of sauna bathing is mentioned in the literature [23, 24]. Our results showed a lowered casual sebum content on the forehead of skin in the RSG.…”
Section: Discussionsupporting
confidence: 68%
“…The concentration of the particles in the hydrogel was 1%, and the size of the particles was 320 nm [6] .…”
Section: Applied Substancesmentioning
confidence: 99%
“…Nanoparticles are an effi cient drug carrier for penetration and storage of topically applied substances in the skin [6,7] . They are often used in medical and cosmetic treatment [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, treatments with glycerol in water reversed skin dryness and erythema. 40 Also, recent findings have proved that glycerol creates a stimulus for barrier repair and improves stratum corneum hydration. 41 That investigation showed that the glycerol effect persists for an extraordinarily long period.…”
Section: Screening Emulsion In Phase-diagram Structurementioning
confidence: 99%